A Conversation on Sexual Rights in India. - Conversation on Sexual Rights in India (2004 : Manesar, India); Creating Resources for Empowerment in Action (Organization : India); SANGAMA (Organization : India); Talking About Reproductive and Sexual Health Issues (Organization : India) (Manesar, Haryana : CREA, 2005)
Proceedings of the two day Dialogue on Sexual Rights in India held i n collaboration of Creating Resources for Empowerment in Action, SANGAM A, and Talking About Reproductive and Sexual Health Issues, Indian orga nizations.
Cover title.
Keywords: Sex and law; Sex crimes; Civil rights -- India -- Congresses